(untitled) (Bangladesh Medical Journal Khulna, 2014)
Tubal and peritoneal factors are related to female infertility by about 25-30%. Through laparoscopy we want to know what are the tubal and peritoneal leading causes and its management related to primary & secondary infertility. Twelve hundred women were selected for laparoscopic evaluation from January 2001 to December 2012 (diagnostic as well as disease correction) those who have no other ovarian, uterine or extra uterine pathology and male factor abnormalities. Under spinal or general anaesthesia, abdomen was distended by C02, 10mm telescope was introduced by sub-umbilical port and another two ports are used for accessories. Before that history taking, general & pervaginal examination, associated relevant investigations were done for exclusion of other causes. Twelve hundred laparoscopy had been done only for detection of tubo-peritoneal causes of infertility. Sixtyseven percent was primary infertility and 33% was secondary infertility. Normal healthy tubes were found in 52% and among the unhealthy tubes, majority were peritubal adhesion (15.8%) followed by unilateral cornual block (12.9%). Treatment given to the patients were adhesiolysis, unilateral or bilateral salphingectomy, salphingostomy and fimbrial dilatation. Hysteroscopic canulation were done in 7 cases. Advice were given for in vitro fertilization & embryo transfer to 71 patients. Pregnancy rate after laparoscopic management was 43% and rest was under observation. Tubal block are more common than in peritubal adhesion. About 50% patient has a history of some form of genital tract infection. Laparoscopy and same sitting hysteroscopic canulation are essential for better pregnancy outcome in patient of proximal tubal block. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18234 Bang Med J (Khulna) 2013; 46 : 16-20